Recurrent Preeclampsia in Women With Metabolic Syndrome and Low Plasma Volume: A Retrospective Cohort Study. Issue 3 (September 2016) - Stekkinger, E.; Scholten, R.R.; Heidema, W.M.; Spaanderman, M.E.A.
Abstract : ( BJOG . 2015;122(13):1773–1780) Preeclampsia occurs in 2% to 8% of pregnancies and is associated with significant maternal and perinatal morbidity and mortality. Women with a history of preeclampsia are at increased risk for preeclampsia in subsequent pregnancies. The aim of this study was to determine the prevalence of recurrent preeclampsia in women who have been diagnosed with metabolic syndrome and/or low plasma volume compared with women who have a history of preeclampsia but neither of these pathologic conditions.